Elicitation and Arrangement of Conceptual Meanings in the Lexicography of Less Documented Languages - Oriikiriza, Celestino (Lexikos, 2014)
The paper demonstrates how some of the dictionaries written in less documented languages, hardly meet the expectations of target users, due to some of the methods used in collecting and arranging meanings of words. The paper, therefore, explains the semantico-syntactic method of eliciting multiple conceptual meanings of words and the alphasyntactico-semantic mode of their arrangement in dictionary making. It concludes by showing how the two methods can lead to compilation of good dictionaries in less documented languages and how the dictionaries would be of benefit to the target users.